Formulation and Antioxidant Activity Test of Emulgel Extract of Guava (Psidium Guajava Linn.) Using DPPH (2,2-Diphenyl-1- Picrylhydrazyl) Methods - Nurain Thomas; Mohamad Aprianto Paneo; Teti Sutriyati Tuloli; Angreni Ayuhastuti; Lutfia Nurfadila Arifin (Jurnal Literasi Mandiri, 2026)
Plants that have the potential to contain antioxidants are guava leaves (Psidium guajava Linn.) which contain one of the compounds, flavonoids, which have antioxidant activity that can reduce free radicals. Emulgel has advantages such as thixotropic, easy to spread, easy to clean, does not leave stains, durable and can be a delivery system for hydrophobic and hydrophilic substances. This study aims to formulate guava leaf extract emulgel and determine antioxidant activity using DPPH method. This research began with guava leaf extraction and base optimization with varying concentrations of stearic acid as an emulsifier consisting of F1 8%, F2 10% and F3 12%. The base that meets the requirements of good physical stability is F2. F2 base was made into emulgel preparations with 3 variations of guava leaf extract concentration, namely F2a 1%, F2b 2% and F2b 3%. The three formulas were tested for physical stability including organoleptic test, emulsion type, pH test, spreadability, adhesiveness, viscosity test, and freeze thaw test as well as antioxidant activity test with DPPH method. The results of the physical stability test showed that the preparations F2a, F2b and F2c met the requirements. The IC50 value in each formulation has a different antioxidant activity value. F2a formulation is 123.59 ppm and F2b is 107.08 ppm which is classified as moderate antioxidant activity, while F2c is 61.74 ppm which is classified as strong antioxidant activity. Guava leaf extract emulgel formula, especially the second formula (F2c), has great potential to be considered by the pharmaceutical industry to be developed into antioxidant products because the results of the evaluation that have been carried out meet the requirements in terms of physical evaluation and potential antioxidant strong.